SINTESIS DAN KARAKTERISASI XEROGEL HASIL KOPRESIPITASI DARI PASIR PANTAI PANJANG BENGKULU - Finni Meyori; Rina Elvia; I Nyoman Candra (University of Bengkulu, 2018)
[SYNTHESIS AND CHARACTERIZATION OF XEROGEL RESULTS OF COPRECIPITATION OF LONG BEACH BENGKULU BEACH]. This research aims to synthesize and characterization to Xerogel which synthesizes from Pantai Panjang sands Bengkulu. The method used for this study to synthesizes Xerogel is to use the coprecipitation method. Qualitative XRF test against raw sand materials that were used show that the content of the element is the most significant element of Si. The first stages of the synthesis of Xerogel is a purification of the sand sample.. Xerogel synthesis is carried out in two phases, namely the manufacture of aqueous solutions of Sodium Silicate and continued with the formation of a gel. The production of Sodium Silicate solution is done using the NaOH concentration at 5, 6 and 7 M. Gel formation process is done by adding a solution of HCl 10 M into the solution of Sodium Silicate, followed by process of filtration, washing and drying in the oven. The results showed that the optimum conditions of synthesis of Xerogel obtained using 6 M NaOH , with a yield obtained is amounting at 0.8%. The results of the test by XRD shows that the silica crystal structure on Xerogel are amorphous-shaped. SEM-EDS test results show that the acquired Xerogel on research has a smooth texture and size is not homogeneous with the highest content of elements are the elements Si and O. PSA test shows that particle size in Xerogel an average at 191.4 nm.